Genomic epidemiology and resistome of Acinetobacter calcoaceticus-baumannii complex in the host and non-hospital environment - Wee, Soon Keong (Nanyang Technological University, 2022)
Acinetobacter baumannii is a recently-emerged nosocomial pathogen that can also cause community-acquired infections (CAI). To date, the origins of CAI and non-hospital sources of A. baumannii are largely unclear, especially in urban tropics. This study aims to characterize A. baumannii and their resistome in the natural non-hospital environment and determine their relatedness with clinical strains. We have characterized local clinical (n = 117) and environmental (n = 97) A. baumannii isolates and found evidence of shared sequence types, such as CAI sequence type (ST10), and acquired resistome in the host and non-hospital environment. Analysis of publicly available data in open genomic databases suggested that plasmids and mobile genetic elements were likely involved in the inter-species dissemination of antimicrobial resistance genes in Acinetobacter calcoaceticus-baumannii complex across different countries. Our observations highlighted the importance of One Health approach to understand the genomic epidemiology and transmission of A. baumannii and its resistome.